PA0833 Is an OmpA C-Like Protein That Confers Protection Against Pseudomonas aeruginosa Infection - Yang, Feng; Gu, Jiang; Zou, Jintao; Lei, Langhuan; Jing, Haiming; Zhang, Jin; Zeng, Hao; Zou, Quanming; Lv, Fenglin; Zhang, Jinyong (Frontiers in Microbiology, 2018)
Pseudomonas aeruginosa is a formidable pathogen that causes infections with high mortality rates. Because of its ability to form biofilms and rapidly acquire resistance to many first-line antibiotics, P. aeruginosa-related infections are typically difficult to cure by traditional antibiotic treatment regimes. Thus, new strategies to prevent and treat such infections are urgently required. PA0833 is a newly identified protective antigen of P. aeruginosa that was identified in a screen using a reverse vaccine strategy in our laboratory. In this study, we further confirmed its protective efficacy in murine sepsis and pneumonia models. Immunization with PA0833 induced strong immune responses and resulted in reduced bacterial loads; decreased pathology, inflammatory cytokine expression and inflammatory cell infiltration; and improved survival. Furthermore, PA0833 was identified as an OmpA C-like protein by bioinformatics analysis and biochemical characterization and shown to contribute to bacterial environmental stress resistance and virulence. These results demonstrate that PA0833 is an OmpA C-like protein that induces a protective immune response in mice, indicating that PA0833 is a promising antigen for vaccine development.